Pendampingan Produksi Video Service Excellence RSIA Bina Medika Tangerang Selatan - Muhammad Dicka Ma'arief Alyatalatthaf; Lobodally Altobeli (ABDIMAS Jurnal Pengabdian Kepada Masyarakat, 2023)
Service Excellence is one of the most important elements for companies that engaged in service fields. Because, service excellence covers almost all processes in B2C (Business to Customer) relationships. In this PKM (Community Service), Institut Teknologi dan Bisnis Kalbis collaborates with RSIA (Rumah Sakit Ibu dan Anak) Bina Medika, Bintaro, South Tangerang. In its service, RSIA Bina Medika has problems in terms of service excellence. RSIA Bina Medika does not yet have a strict and integrated standarization. Thus, this PKM aims to provide intensive assistance to partners in producing Service Excellence videos through three stages of assistance: pre-production, production, and post-production.